A case report and literature review on fabella syndrome after high tibial osteotomy. Issue 4 (January 2018) - Kim, Taehun; Chung, Haksun; Lee, Hyungmin; Choi, Young; Son, Jung-Hwan
Abstract: Rationale: The fabella is a normal structure, but is occasionally reported to cause posterior knee pain. The aim of this study was to present fabella syndrome after high tibial osteotomy. Patient concerns: A 55-year-old female patient was admitted to the hospital due to about 1 year and 8 months of left knee pain. Sclerosis was observed in the anterior margin of the fabella in the preoperative magnetic resonance (MR) T2 image, and reactive bone marrow was found and was considered to be due to degeneration of the distal femur. Degenerative change (Kellgren and Lawrence—KL grade 2) of the left knee was observed, along with cartilage delamination corresponding to International Cartilage Repair Society (ICRS) grade 4 in the patellofemoral joint. Diagnoses: We present the first reported case of fabella syndrome in Korea, after high tibial osteotomy due to degenerative arthritis and varus deformity, rather than artificial joint surgery. Interventions: We excised the fabella from the patient's knee. Outcomes: There was no evidence of recurrence during 5 months of postoperative follow-up. Posterolateral Corner including the fabella might have sustained increased tensile force causing symptoms due to compression of the fabella by the posterior joint of the posterior femoral condyle. Lessons: We present the first reported case of fabella syndrome in Korea, after high tibial osteotomy due to degenerative arthritis and varus deformity, rather than artificial joint surgery. Collision syndrome caused by a fabella has previously been attributed to inconsistency of the joint surface due to excessive exercise and degenerative changes due to knee instability. We report this case since it appeared to involve collision syndrome due to mechanical change of an angular deformity.